ANALISIS KADAR KALSIUM (Ca) DAN FOSFOR (P) PADA DAUN KECIPIR (Psophocarpus tetragonolobus L) DI PULAU AMBON DAN SERAM BAGIAN BARAT - Tryvena Lesnussa; Nikmans Hattu; Yeanchon H Dulanlebit (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2019)
One of the leaves that can be consumed to fill nutritional need for people’s is kecipir leaves (Phosphocarpus tetragonolobus L). This leave contains minerals among them caloium, potassium and phosphorus but the level is calcium potassium and phosphorus at kecipir not yet know. Therefor this study was making conduoted to find out level of caloium, potassium and phosphorus in kecipir leave at two different location that is Urimesing village and Eti village. Calcium and potassium levels are analyzed SSA while phosphorus levels are analyzed UV-VIS analysis result indicate calcium, potassium, phosphorus level in kecipir leaves at urimeseng village is 904,25 mg/100g, is 100,46 mg/100g and calcium potassium, phosphorus levels in kecipir leave at Eti village is 1.162,59 mg/100g and 190,498 mg/100g. based on these result obtained calcium, potassium and phosphorus levels with different values from each sampling location. This happened because of geographic location, soil structure and water content greatly affect the levels of calcium, potassium, and phosphorus.